How do reinforcers affect choice? Preference pulses after responses and reinforcers. Issue 1 (1st June 2017) - Gomes‐Ng, Stephanie; Elliffe, Douglas; Cowie, Sarah
Abstract : In concurrent schedules, reinforcers are often followed by a brief period of heightened preference for the just‐productive alternative. Such 'preference pulses' may reflect local effects of reinforcers on choice. However, similar pulses may occur after nonreinforced responses, suggesting that pulses after reinforcers are partly unrelated to reinforcer effects. McLean, Grace, Pitts, and Hughes (2014) recommended subtracting preference pulses after responses from preference pulses after reinforcers, to construct residual pulses that represent only reinforcer effects. Thus, a reanalysis of existing choice data is necessary to determine whether changes in choice after reinforcers in previous experiments were actually related to reinforcers. In the present paper, we reanalyzed data from choice experiments in which reinforcers served different functions. We compared local choice, mean visit length, and visit‐length distributions after reinforcers and after nonreinforced responses. Our reanalysis demonstrated the utility of McLean et al.'s preference‐pulse correction for determining the effects of reinforcers on choice. However, visit analyses revealed that residual pulses may not accurately represent reinforcer effects, and reinforcer effects were clearer in visit analyses than in local‐choice analyses. The best way to determine the effects of reinforcers on choice may be to conduct visit analyses in addition to local‐choice analyses.